Fullerene derivative induced morphology of bulk heterojunction blends: PIPCP:PC61BM. Issue 8 (30th January 2019) - Huang, Tzu-Yen; Yan, Hongping; Abdelsamie, Maged; Savikhin, Victoria; Schneider, Sebastian A.; Ran, Niva A.; Nguyen, Thuc-Quyen; Bazan, Guillermo C.; Toney, Michael F.
Abstract : The performance of organic solar cells depends on the morphology in bulk heterojunctions, including the polymer degree of crystallinity and the amount of each phase: aggregated donor, aggregated acceptor and molecularly mixed donor : acceptor phase. Abstract : The performance of organic solar cells (OSCs) depends crucially on the morphology in bulk heterojunctions (BHJs), including the degree of crystallinity of the polymer and the amount of each material phase: aggregated donor, aggregated acceptor, and molecular mixed donor : acceptor phase. In this paper, we report the BHJ morphology of as-cast blend films incorporating the polymer PIPCP as the donor and [6, 6]-phenyl-C61 -butyric acid methyl ester (PC61 BM) as the acceptor. Tracking the scattering intensity of PC61 BM as a function of PC61 BM concentration shows that PC61 BM aggregates into donor-rich domains and there is little to no phase where the PC61 BM and PIPCP are intimately mixed. We further find that on blending the scattering peak due to PIPCP ordering along the backbone increases with decreasing PIPCP fraction, which is attributed to improved ordering of PIPCP due to the presence of PC61 BM. Our results suggest that the improved ordering of PIPCP along the backbone (consistent with an increased conjugation length) with blending contributes to the observed low open-circuit voltage energy loss.